Influence Of Partings In A Coal Seam On Long Term Pillar Stability - K. Biswas (International Conference on Ground Control in Mining, 1995)
So far, all pillar design methods or approaches consider the coal seam as a uniform structure From some mine visits in northern Appalachian Region. it is found that some coal seams have binder or parting material within the coal scan with varying thicknesses and numbers- And it has also been found that these kinds of hinder materials tire prone to weathering when exposed to ambient mine moisture In this paper an attempt has been made to study the weathering susceptibility of parting materials and coal when exposed to moisture and a two dimensional finite element analysis has been carried out to study the effect of the presence of partings on the structural integrity of the coal pillar in terms of short-term and long-term stability.